Evaluación de la incidencia Meloidogyne graminicola en el cultivo de arroz (Oryza sativa) en el cantón Urdaneta - Bajaña Fajardo, Edison Javier (2024)
Rice cultivation is crucial for food security and the economy of Ecuador, but the presence of the nematode M. graminicola poses a challenge in Urdaneta Canton. This study aims to assess the incidence and distribution of the nematode to comprehend its impact on rice cultivation. The hypothesis posits that the presence of M. graminicola affects rice yield in the canton. The study involves a comprehensive literature review on the nematode's biology, symptoms, damages, and rice production systems. The importance of the research is justified to develop integrated management strategies and promote agricultural sustainability. The summary encompasses both the research proposal and the abstract, highlighting the study's relevance for food security and economic development in Urdaneta.